IL-6 and TNFα Drive Extensive Proliferation of Human Tregs Without Compromising Their Lineage Stability or Function - Skartsis, Nikolaos; Peng, Yani; Ferreira, Leonardo M. R.; Nguyen, Vinh; Ronin, Emilie; Muller, Yannick D.; Vincenti, Flavio; Tang, Qizhi (Frontiers in Immunology, 2021)
Treg therapies are being tested in clinical trials in transplantation and autoimmune diseases, however, the impact of inflammation on Tregs remains controversial. We challenged human Tregs ex-vivo with pro-inflammatory cytokines IL-6 and TNFa and observed greatly enhanced proliferation stimulated by anti-CD3 and anti-CD28 (aCD3/28) beads or CD28 superagonist (CD28SA). The cytokine-exposed Tregs maintained high expression of FOXP3 and HELIOS, demethylated FOXP3 enhancer, and low IFNg, IL-4, and IL-17 secretion. Blocking TNF receptor using etanercept or deletion of TNF receptor 2 using CRISPR/Cas9 blunted Treg proliferation and attenuated FOXP3 and HELIOS expression. These results prompted us to consider using CD28SA together with IL-6 and TNFa without aCD3/28 beads (beadless) as an alternative protocol for therapeutic Treg manufacturing. Metabolomics profiling revealed more active glycolysis and oxidative phosphorylation, increased energy production, and higher antioxidant potential during beadless Treg expansion. Finally, beadless expanded Tregs maintained suppressive functions in vitro and in vivo. These results demonstrate that human Tregs positively respond to proinflammatory cytokines with enhanced proliferation without compromising their lineage identity or function. This property can be harnessed for therapeutic Treg manufacturing.